2022
DOI: 10.3390/ijfs10040089
|View full text |Cite
|
Sign up to set email alerts
|

Working Capital Management and Shareholder’s Wealth Creation: Evidence from Manufacturing Companies Listed in Oman

Abstract: Working capital management (WCM) is a key factor in the success of manufacturing companies when credit is restricted, as is the case in the current climate caused by the COVID-19 crisis. The main purpose of this paper is to investigate the relationship between working capital management, earnings quality, sales growth, and shareholders’ wealth of listed manufacturing firms in Oman. The study used balanced panel data of 31 manufacturing firms listed on the Muscat Stock Exchange (MSE) from 2004 to 2019. The stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 73 publications
0
9
0
1
Order By: Relevance
“…(2021) and Njoroge and Opuodho (2022), showed that APP improved firm profitability. Also, Panigrahi et al . (2022) found that the payment deferred period increased the financial performance of manufacturing firms in Oman.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 95%
See 3 more Smart Citations
“…(2021) and Njoroge and Opuodho (2022), showed that APP improved firm profitability. Also, Panigrahi et al . (2022) found that the payment deferred period increased the financial performance of manufacturing firms in Oman.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 95%
“…Other studies, such as Gonçalves et al (2018), Omar et al (2021), Panda et al (2021) and Njoroge and Opuodho (2022), showed that APP improved firm profitability. Also, Panigrahi et al (2022) found that the payment deferred period increased the financial performance of manufacturing firms in Oman. Similarly, Njoroge and Opuodho (2022) uncovered that creditors' management practices enhanced firm performance in Kenya.…”
Section: Literature Review and Hypotheses Development 21 A Brief Over...mentioning
confidence: 97%
See 2 more Smart Citations
“…For Ethiopian exporting firms, Wassie [ 49 ] observed a positive CCC-ROA relationship. Panigrahi et al [ 29 ] suggested that CCC has a positive impact on ROA while days in WC have a negative impact. In the study of Korent and Orsag [ 50 ], higher profitability of firms in Croatia is related to CCC.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%